Front Cover Picture: Indene Derived Phosphorus‐Thioether Ligands for the Ir‐Catalyzed Asymmetric Hydrogenation of Olefins with Diverse Substitution Patterns and Different Functional Groups (Adv. Synth. Catal. 19/2021). Issue 19 (17th September 2021) - Margalef, Jèssica; Biosca, Maria; de la Cruz‐Sánchez, Pol; Caldentey, Xisco; Rodríguez‐Escrich, Carles; Pàmies, Oscar; Pericàs, Miquel A.; Diéguez, Montserrat
Abstract : The front cover picture, designed by Jèssica Margalef, illustrates the usefulness of a modular and easy‐to‐assemble catalyst design for asymmetric hydrogenation. By choosing the appropriate sulfur and phosphorus substituents on new Ir‐P, S‐catalysts, it is possible to hydrogenate substrates of very different nature (50 olefins in total). Improving on most catalysts reported so far, di‐ and E / Z ‐trisubstituted olefins with a variety of functional groups and coordination ability can be reduced with excellent enantioselectivities. Details can be found in the Research Article by Diéguez and co‐authors (J. Margalef, M. Biosca, P. de la Cruz‐Sánchez, X. Caldentey, C. Rodríguez‐Escrich, O. Pàmies, M. A. Pericàs, M. Diéguez, Adv. Synth. Catal . 2021, 363, 4561–4574; DOI: 10.1002/adsc.202100069 )